Effect of implementing childbirth preparation classes on women's self-efficacy and pregnancy outcomes - Awatiful Azza; Zusana A Sasarari; Nurafriani Nurafriani; Irmawati S; Muh Yunus (Jurnal Ilmiah Kesehatan Sandi Husada)
Introduction: Childbirth preparation classes play a crucial role in equipping pregnant women with the knowledge and skills necessary to face labor with confidence. Low maternal self-efficacy is often associated with increased anxiety, longer labor duration, and negative birth experiences. This study examines how implementing childbirth preparation classes affects women’s self-efficacy and pregnancy outcomes.